A study of the level of satisfaction of user on bridge management system : case study, Penang Second Bridge - Muhammad Fikri, Norsaidi (2017)
Bridge are structures that require continual, arduous attentions and organized inspections in order to prevent calamity. Comprehensive preventative measures and maintenance that were invested will definitely help to diminish the cost incurred not only repair but also on other losses that might be caused due to structural collapse. Therefore, maintenance management is vital and greatly needed to sustain their functions for the safety of all users and in maintaining their comfort and confidence while using the bridge. With regards to this, a study on procedure and bridge inspection was conducted to identify damages in bridge structure and also gauge the level of satisfaction of users of the Penang Second Bridge. The data was collected via questionnaires develop for the bridge users and also the maintenance management unit of JKSB. Based on the case study, work maintenance on the bridge constitutes are routine maintenance, heavy repair work, upgrading work, and bridge inspection. JKSB maintenance management was using Integrated Asset Management System (IAMS) to maintain their bridge. The study identified the main damage on the bridge are pothole and spalling. It also showed that majority of the bridge users are satisfied with the maintenance work carried out.